Organizational support versus supervisor support: The impact on hospitality managers' psychological contract and work engagement. (May 2020) - Shi, Xiaolin (Crystal); Gordon, Susan
Highlights: This study considered perceived organizational support (POS) and perceived supervisor support (PSS) at the same time and explored which one is more critical in influencing hospitality employees' psychological contract (PC) and work engagement. A 2 (PSS: high vs. low) × 2 (POS: high vs. low) between-subjects experimental study was conducted. Participants were randomly assigned to one of the four experimental scenarios and answered the questions accordingly. Instead of focusing on the sequential relationship, this study explores the contemporaneous relationship of PSS and POS. This study enriches the field of perceived support by considering the situations in which the levels of the two types of support could vary and even been opposite. The findings in this study indicate that PSS could be a more important factor than POS to influence managers' PC and work engagement in the hospitality industry. Executives also need to be trained on the concept of PC and understand that statements made in times of recruitment, one-on-one meetings, performance reviews, etc. can be perceived as promises by managers and thus later perceived as being fulfilled or breached. Directors and HR should be forthcoming with managers so that not only are psychological promises seen as fulfilled, but support is extended through actions such as valuing opinions, considering goals, and caring about satisfaction at work. Abstract: Considering perceived organizational support (POS) and perceived supervisor support (PSS) at the same time and understanding which one is more critical receives little attention. A scenario-based experimental design was conducted to examine the influences of high PSS & low POS and low PSS & high POS on hospitality employees' psychological contract (PC) and work engagement. The results show that managers experience both psychological contract breach (PCB) and lower work engagement under these two imperfect situations. Furthermore, managers have relatively higher PCB and lower work engagement under the situation of receiving lower PSS than receiving lower POS. Finally, it was found that PCB has a more negative influence on managers' work engagement when receiving lower PSS. Theoretical and practical implications based on the results are discussed.